2020
DOI: 10.1515/dmdi-2020-0127
|View full text |Cite
|
Sign up to set email alerts
|

Drug–drug interaction of rivaroxaban and calcium channel blockers in patients aged 80 years and older with nonvalvular atrial fibrillation

Abstract: ObjectivesFor revealing the peculiarities of the drug–drug interaction of rivaroxaban (substrate CYP3A4 and P-gp) and calcium channel blockers (CCBs) (verapamil – inhibitor CYP3A4 and P-gp and amlodipine – substrate CYP3A4) in patients 80 years and older with nonvalvular atrial fibrillation (NAF) we studied 128 patients.MethodsAll patients were divided into groups depending on the therapy taken: the 1st – rivaroxaban + amlodipine (n=51), the 2nd – rivaroxaban + verapamil (n=30), the control group – rivaroxaban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In this study, we chose eleven commonly prescribed cardiovascular drugs for our first stage of DDI evaluation: verapamil, diltiazem, nifedipine, amlodipine, amiodarone, quinidine, propafenone, irbesartan, valsartan, benazepril and captopril (as a control drug not metabolized by liver enzymes). Unexpectedly, the preliminary in vitro evaluation results showed that amlodipine and nifedipine exhibited the highest inhibitory effect (with more than 5-fold) on vonoprazan, while other CYP3A4 inhibitors, verapamil, diltiazem and amiodarone only exhibited slightly increased inhibition effects, although they were reported to have the same ( Zhou, 2008 ) or even stronger ( Sychev et al, 2020 ) inhibition on CYP3A4 than that of amlodipine or nifedipine. Next, we evaluated the IC 50 values of amlodipine and nifedipine that reconfirmed their inhibition effects on vonoprazan in both RLMs and HLMs, showing a stronger inhibition in HLMs.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we chose eleven commonly prescribed cardiovascular drugs for our first stage of DDI evaluation: verapamil, diltiazem, nifedipine, amlodipine, amiodarone, quinidine, propafenone, irbesartan, valsartan, benazepril and captopril (as a control drug not metabolized by liver enzymes). Unexpectedly, the preliminary in vitro evaluation results showed that amlodipine and nifedipine exhibited the highest inhibitory effect (with more than 5-fold) on vonoprazan, while other CYP3A4 inhibitors, verapamil, diltiazem and amiodarone only exhibited slightly increased inhibition effects, although they were reported to have the same ( Zhou, 2008 ) or even stronger ( Sychev et al, 2020 ) inhibition on CYP3A4 than that of amlodipine or nifedipine. Next, we evaluated the IC 50 values of amlodipine and nifedipine that reconfirmed their inhibition effects on vonoprazan in both RLMs and HLMs, showing a stronger inhibition in HLMs.…”
Section: Discussionmentioning
confidence: 97%
“…The risk of bleeding was evidenced shortly after DDIs exposure and logically increased over time. Some factors such advanced age, renal failure, or severe inflammatory syndrome can significantly modulate the magnitude of pharmacokinetic DDIs [63][64][65]. Furthermore, unexpected DDIs could occur.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…In the study on the effect of single nucleotide polymorphism of ABCB1 gene on in-vitro pharmacokinetics of rivaroxaban, it was shown that 3435C>T polymorphism of ABCB1 gene had no significant effect on intracellular accumulation of rivaroxaban compared to normal genotype [21]. In another study by Sychev et al [22] devoted to the assessment of the risk of interdrug interaction between rivaroxaban and slow calcium channel blockers in patients with nonvalvular atrial fibrillation over 80 years old, the data were obtained that in the group of patients taking rivaroxaban together with CYP3A4 and glycoprotein P inhibitor verapamil, prothrombin time, residual equilibrium concentration and the incidence of clinically significant minor bleeding were significantly higher compared with the group of patients taking rivaroxaban with amlodipine and the control group taking rivaroxaban alone [22].…”
Section: Introductionmentioning
confidence: 99%